Synthesis of 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives in a reusable catalyst/solvent; 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) - Farzaneh Mohamadpour (Current Research in Green and Sustainable Chemistry)
A green method of producing 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives is shown. It makes use of polyfluorinated alcohol as a reusable catalyst/solvent and the Knoevenagel-Michael cyclic condensation mechanism. This procedure complies with green chemistry guidelines. The reactions can be completed in a lot less time and produce products with exceptional yields. Safe reactions are used in this environmentally friendly approach, which eliminates the requirement for column chromatographic separation. It is also simple to create and work up, inexpensive, and cost-effective. Furthermore, green 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) is highly stable and does not significantly change or lose its effectiveness when utilized four more times. Because of this, it's highly helpful for preserving the environment when doing industrial operations.